2015
DOI: 10.1002/2015jc011306
|View full text |Cite
|
Sign up to set email alerts
|

Remote alongshore winds drive variability of the California Undercurrent off the British Columbia‐Washington coast

Abstract: The California Undercurrent transports warm, salty, nutrient‐rich, oxygen‐depleted water along the continental slope from the equatorial Pacific to the Aleutian Islands. We use multiyear acoustic Doppler current profiler records collected simultaneously at two mooring sites off Vancouver Island to detail the regional structure of the undercurrent and to show that much of its variability is attributable to the passage of remotely forced, coastal‐trapped waves. We also document two subsurface currents missed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 29 publications
(50 reference statements)
4
14
0
Order By: Relevance
“…Previous research evidences the relevance of the local wind on the generation of coastal undercurrents [McCreary, 1981;Philander and Yoon, 1982;Yoon and Philander, 1982]. Nonetheless, in agreement with subsequent studies that exhibit the relevance of remote forcing on the CU dynamics [Connolly et al, 2014;Thomson and Krassovski, 2015], our results show that the tropical dynamics dominates the seasonal variability of the Southern CU. Yoshida [1967] proposes that the equatorial dynamics can influence the dynamics of eastern boundary undercurrents, we found that the seasonal CU variability along the SCCS is dominated by the equatorial dynamics through the generation of semiannual Kelvin waves that reach the coast and travel poleward as Semiannual Coastal-Trapped Waves.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Previous research evidences the relevance of the local wind on the generation of coastal undercurrents [McCreary, 1981;Philander and Yoon, 1982;Yoon and Philander, 1982]. Nonetheless, in agreement with subsequent studies that exhibit the relevance of remote forcing on the CU dynamics [Connolly et al, 2014;Thomson and Krassovski, 2015], our results show that the tropical dynamics dominates the seasonal variability of the Southern CU. Yoshida [1967] proposes that the equatorial dynamics can influence the dynamics of eastern boundary undercurrents, we found that the seasonal CU variability along the SCCS is dominated by the equatorial dynamics through the generation of semiannual Kelvin waves that reach the coast and travel poleward as Semiannual Coastal-Trapped Waves.…”
supporting
confidence: 92%
“…Previous research based on observations with limited resolution, or coverage, to detect the propagation of SCTW has associated the semiannual CU variability to the local dynamics off Southern California [Hickey, 1979;Chelton, 1984;Lynn and Simpson, 1987;Gay and Chereskin, 2009]. Subsequent studies, however, reveal that remote wind-induced anomalies propagate as coastal-trapped waves and play a key role on the CU dynamics [Connolly et al, 2014;Thomson and Krassovski, 2015]. In addition, [Frischknecht et al, 2015] evidence that, by the same propagating mechanism, the equatorial dynamics dominates the near-shore temperature, salinity, and biogeochemical variability along the subsurface California Current System during El Niño periods.…”
Section: Introductionmentioning
confidence: 99%
“…It becomes unstable and feeds jets and eddies into the coastal transition zone (CTZ) [Brink and Cowles, 1991] merging with CCS. Along the coast in WA and BC upwelling winds are relatively weaker than in OR and Northern CA [Foreman et al, 2011] and shelf and slope dynamics on temporal scales of several days and longer are strongly influenced by remotely generated coastally trapped waves (CTW) [Connolly et al, 2014;McCabe et al, 2015;Thomson and Krassovski, 2015]. In Southern CA, winds are generally weak and coastal ocean variability on subtidal time scales can be influenced notably by CTW propagating from Mexico [Enfield, 1987].…”
Section: Introductionmentioning
confidence: 99%
“…Part of the reason for this inconsistency is likely the occurrence of the major El Niño event in 1982 and the relatively short data record used. A recent analysis by Thomson and Krassovski [2015] using an intermediatelength current record (2010)(2011)(2012)(2013)(2014) from southern Vancouver Island found evidence for CTW variability at 10-40 day periods but little evidence of direct CTW variability beyond a period of 40 days. Pringle and Riser [2003] presented one of the very few observationally based works relating ocean temperatures and remote wind stress with regard to CTWs.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the central CalCS, the northern extent of the CalCS, along southern Vancouver Island, has received less attention with respect to CTW influence. Noteworthy exceptions include Crawford and Thomson [1982], Yao et al [1984], Denbo and Allen [1987], Connolly et al [2014], and Thomson and Krassovski [2015]. Crawford and Thomson [1982] showed that the continental shelf and slope off southern Vancouver Island allow first-mode diurnal frequency barotropic shelf waves and attributed fluctuations in diurnal currents to them.…”
Section: Introductionmentioning
confidence: 99%